Relationship between quantity of IFNT estimated by IFN-stimulated gene expression in peripheral blood mononuclear cells and bovine embryonic mortality after AI or ET - Matsuyama Shuichi; Kojima Takatoshi; Kato Satoru; Kimura Koji (BMC, 2012)
Abstract Background Interferon tau (IFNT), which is secreted into the uterine cavity during the maternal recognition period (MRP), is a key factor for establishment of pregnancy. The present study aims to clarify the relationship between the ability of a bovine conceptus to produce IFNT during the MRP and the conceptus's ability to establish pregnancy. Methods In the first experiment, IFNT (0, 500, or 1000 micrograms) was administered into the uterine horn ipsilateral to the CL 16 or 17 d after standing estrus, and mRNA levels of IFN-stimulated gene 15-kDa protein (ISG15) and Mx2 in peripheral blood mononuclear cells (PBMCs) were determined. In the second experiment, we investigated ISG15 mRNA expression in PBMCs during the MRP in cattle after either artificial insemination (AI) or embryo transfer (ET). Results Intrauterine administration of IFNT stimulated ISG15 and Mx2 gene expressions in PBMCs in cattle, and there was a positive correlation between the expressions of peripheral markers and the quantity of IFNT administered. In pregnant and normal interestrous interval (< 25 d) cattle (nIEI cattle), expression levels of the ISG15 gene showed similar patterns after AI and ET, and ISG15 mRNA expression was increased in pregnant cattle but unchanged in nIEI cattle. In contrast, ISG15 gene expression in extended interestrous interval (greater than or equal to 25 d) cattle (eIEI cattle) differed after ET compared with AI. In eIEI cattle after ET, ISG15 gene expression increased, such that the value on day 18 was intermediate between those of pregnant and nIEI cattle. In eIEI cattle after AI, ISG15 gene expression did not increase throughout the observation period. Conclusions The results of the current study indicate that the quantity of conceptus-derived IFNT can be estimated by measuring ISG15 mRNA levels in PBMCs from cattle. Using this approach, we demonstrate that ISG15 gene expression during the MRP in eIEI cattle differed after ET compared with AI. In addition, the modest increase in ISG15 gene expression in eIEI cattle after ET suggests that late embryo losses were due to delayed or insufficient growth of the conceptus during the MRP in cattle.